A model for the macro- and microstructure of a Yipunu-French school dictionary - Mabika Mbokou, Ludwine (Stellenbosch : University of Stellenbosch, 2006)
Thesis (DLitt (Afrikaans and Dutch))--University of Stellenbosch, 2006.